PRAKTIK SUAP DALAM PERSPEKTIF HUKUM DAN DAMPAKNYA TERHADAP KEADILAN SOSIAL - Mohamad Ikbal Kadir; Moh Syaril Lasena; Isra Salsabila Hamid (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2026)
Bribery is a phenomenon that undermines the integrity of the legal system and hinders the realization of social justice. From a legal perspective, bribery is classified as a corruption offense that contradicts the principles of transparency, accountability, and equality before the law. This practice not only disrupts the process of fair law enforcement but also reduces public trust in state institutions and weakens the legitimacy of the government. The social impacts of bribery include unequal access to resources and public services, as well as disparities in the fulfillment of individual rights, particularly among marginalized groups. This study aims to analyze bribery practices from a legal perspective and examine their implications for social justice through a literature review of relevant regulations and policies. The findings indicate that strengthening consistent law enforcement, combined with community empowerment, is an effective strategy to reduce bribery practices and promote sustainable social justice